Keeping the archives above water: preserving regional heritage in times of accelerated climate change - Wessell, Adele; Thorpe, Clare (Archival science, 2023)
The critical question of how sustainability and resilience can inform archival practice in regional communities is motivated by the experience of flooding in Lismore, Australia, which exposed the vulnerability of local archives to the effects of climate change and the limitations of local infrastructure. Regional historical societies and community organisations serve as a repository for the history of particular communities, preserving records, artefacts and other materials that document the unique stories and experiences of that place. Collections are independently curated and generally run by volunteers but poorly resourced with insufficient space. They are more likely to be subject to extreme weather events that disproportionately impact regional Australia compared to its cities. Regional collections fall outside national strategies for sustainability, digitisation or investment. Without urgent attention to the fate of regional archives, local heritage is under threat, and with it, an understanding of how that history contributes to the national past and the connection to place and community. This paper explores regional archives from the perspective of the local historical records of Lismore, Northern New South Wales, where flooding is a familiar experience that has reached a new intensity in recent years.